CAVT a congestion avoidance visualization tool. - Welzl, Michael (Computer communication review.)
We present CAVT, a simple yet powerful tool to visualize the behavior of congestion control mechanisms. Essentially being a simulator that builds upon the well-known Chiu/Jain vector diagrams, CAVT provides researchers, teachers and students with a new abstraction level that has already shown its value in practice.